Economic Expertise in Insolvency (Bankruptcy) Procedures: Significance and Problems - D. O. Yarovoy (Теоретическая и прикладная юриспруденция)
The article is devoted to the consideration of the significance of forensic inquiry used in insolvency (bankruptcy) cases. In particular, the financial and economic expertise is considered. The significance and tasks of financial and economic expertise are determined. The law enforcement practice in the appointment of financial and economic expertise is considered. The issue of not improving existing methods for conducting financial and economic expertise is considered.